Detection and perception of generic host volatiles by mosquitoes modulate host preference: context dependence of (R)-1-octen-3-ol. Issue 11 (November 2016) - Majeed, Shahid; Hill, Sharon Rose; Birgersson, Göran; Ignell, Rickard
Abstract : Natural selection favours a restricted host breadth in disease vector mosquitoes, indicating that there is an adaptive value associated with maintaining plasticity in host preference. One mechanism to maintain such plasticity is via the detection of generic cues by conserved peripheral olfactory pathways, which when perceived in different host odour contexts enable the identification of and discrimination among potential host species. Here, we show that the context of an odour cue shapes host perception in mosquitoes, by altering the release rate of the generic host-related volatile ( R )-1-octen-3-ol, within its natural range, and in the background odour of known hosts and non-hosts. This result highlights that host recognition is contextual and dependent on quantitative and qualitative differences in odour blends and the olfactory codes evoked. From the perspective of vector management, understanding the perception of odour blends and their context is essential to the process of developing synthetic blends for the optimal attraction of mosquitoes in efforts to control and monitor populations.